Development and quality assessment of gluten-free cookies using rice flour and date fruit - Akram, Sajeela; Chatha, Aqsa; Abid, Juweria; Farooq, Umar; Ahmad, Abdul Momin Rizwan (Frontiers in Nutrition, 2025)
IntroductionBakery products formulated with wheat flour as the major constituent are unfit for consumption for people with gluten sensitivity. Hence, there is a need to utilize other substitutes as a major ingredient in food commodities for individuals suffering from gluten sensitivity or celiac disease, without compromising consumer acceptability.ObjectiveThe objective of the current study was to develop gluten-free cookies by partial substitution of the cookie’s rice flour with date fruit pulp and pit powder.MethodsCookies were formulated by adding 100 g rice flour, 13.5 g eggs, 54 g sugar, 49.5 g shortening, and 2–3 drops of vanilla essence. Moreover, the proportion of date fruit pulp/date paste was 20, 40, 60, 80, and 100%, respectively, in groups T1, T2, T3, T4, and T5. Similarly, the proportion of date pit powder varied from 5, 10, 15, 20, and 25%, respectively, in groups T1, T2, T3, T4, and T5. Nutritional (proximate) composition, physical attributes, and sensory parameters of the prepared cookies were determined. Data were analyzed statistically using ANOVA and compared using Tukey’s Least Significance Difference (LSD).ResultsThe utilization of date paste and pit powder improved the proximate composition of cookies with increasing levels of added paste, whereas physical parameters showed a decrease in values with increasing levels of substitution. Organoleptic characteristics exhibited that biscuit quality was acceptable under various treatments.ConclusionRice-based cookies with added date fruit and pit powder could be a practical and acceptable substitute for individuals with gluten sensitivity.